Informational Nudges and Environmental Preferences in a Public Goods Game in Networks - Ouvrard, Benjamin; Stenger, Anne (Environmental modeling & assessment, 2024)
Using a framed lab experiment, we test whether the efficiency of a pro-environmental informational nudge (disclosure of the socially optimal level of investment) depends on subjects’ environmental preferences and on the type of network they belong to. We observe a higher coordination on the socially optimal profile of investments in the circle network (everyone has the same number of neighbors), but only with the most sensitive subjects to environmental matters. In star networks (some have more neighbors than the other members), we find evidence that the nudge can even induce a decrease in the level of investments for the least sensitive subjects. Thus, nudges should be aimed at individuals with high environmental sensitivity in networks favoring uniform behavior.